(untitled) (Bangladesh Journal of Urology, 2020)
Purposes: To compare the efficacy of ultrasound and CT scan in renal tumour evaluation and to establish by subsequent histopathology. Introduction : Renal cell carcinoma accounts for about 3 % of all adult neoplasms. In detecting, characterizing and staging of renal tumours cross-sectional imagings are essential. Methods: In this study 36 cases were selected nonrandomly irrespective of age and sex according to selection criteria. The study was conducted from June 2006 to May 2007 in Banga Bandhu Sheikh Mujib Medical University and other Hospitals in Dhaka City in the department of urology on a quasi- experimental basis. After counselling and taking consent all patients were evaluated clinically and by ultrasound and CT scan. All patients underwent surgery followed by histopathology. All informations were collected in a predesigned data collection sheet. Data were analyzed by computer software program-SPSS version 12 and by manual technique. Comparison and correlation between Ultrasonogram and CT findings were done by Chi-square test. Level of significance was expressed as P-value. Results: Among 36 patients 21 were male and 15 female with a ratio of 1.4:1, age ranging from 3 to 73 years. In this study (from the data) 94.44%, 33.33%, 89.74% and 100%, 66.66% 97.43% respectively. And there was no statistical significance between these two imaging findings in renal tumour evaluation and P- Value was > 0.10 so it was not Significant. Conclusion : Ultrasonogram and CT Scan are near equivalent to each other evaluation of renal tumour. Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.55-57